Statistical model of kinematic indicators of performing an element on the parallel bars in gymnastics - Kolesnikova, E.S.; Parahin, V.A.; Ivashina, V.V.; Sobitova, M.Z. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop a statistical model of the kinematic parameters of the elements with a large swing forward on uneven bars of different heights based on the identification of differences in the structure of the element performed by gymnasts of the Russian national team and the world's leading gymnasts at competitions of various ranks (2020-2024). Results and conclusions. The conducted research shows that the technique of performing the 360° rotation element performed by the world's leading gymnasts creates favorable conditions for transferring the skill to performing the 540° rotation element (Russian gymnasts performed the element at competitions of various ranks – 0 times, gymnasts from other countries – 34 times). In this regard, the kinematic parameters of the whole 360° rotation element performed by foreign gymnasts can be considered as a model.